Stock Selection in Constructing Halal Food And Beverage Indices For Indonesia Stock Exchange - Yustria, Deri; Bintoro, Bambang P.K. (The Indonesian Journal of Business Administration, 2015)
Abstract.Islamic Capital Markets in Indonesia shows a significant development, however, the crucial trade infrastructure such as sectoral indices are still not available. Index function is very important in stock trading, for investors, regulators, analysts and fund managers to measure the performance a group of stocks. Currently there had been Indonesia Sharia Stock Index (ISSI) which was published in 2011 and JII (Jakarta Islamic Index) are actually already present in 2000. But the market needs the other sharia indices to increase the number of sharia product. Industrial sectors which have the basis for constructing new Islamic index are very wide and some have great potential promising. Strategic sectors of the economy in many countries with Muslim population base, shows a very remarkable performance. With a number of the largest Muslim population in the world, Indonesia clearly has a huge opportunity, one of them by developing consumer goods industry specifically, the halal food and beverages. This sector can be explored and developed through the financial sector, especially in the capital market. The presence of Sharia Stock Index based halal food and beverages business will strengthen the Islamic capital market industry in Indonesia, including the exciting growth issuers, increasing the number of investors and multiply the Sharia mutual fund products. This study aims to construct new sharia indices, so there is a need for a decision-making technique by the Indonesia Stock Exchange to facilitate the process of selecting stocks that deserve to be the Islamic stock companies in the food and beverage industry. Although it is not as easy as making a regular sectoral indices carried by classifying stocks based on its core business, constructing halal food and beverage indices needs to be established in a clear and structured process so that the indices applicable for IDX.Ã‚Â